2021
DOI: 10.1038/s41467-020-20168-2
|View full text |Cite
|
Sign up to set email alerts
|

Robust and efficient hydrogenation of carbonyl compounds catalysed by mixed donor Mn(I) pincer complexes

Abstract: Any catalyst should be efficient and stable to be implemented in practice. This requirement is particularly valid for manganese hydrogenation catalysts. While representing a more sustainable alternative to conventional noble metal-based systems, manganese hydrogenation catalysts are prone to degrade under catalytic conditions once operation temperatures are high. Herein, we report a highly efficient Mn(I)-CNP pre-catalyst which gives rise to the excellent productivity (TOF° up to 41 000 h−1) and stability (TON… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 53 publications
4
89
0
Order By: Relevance
“…In contrast, populations at the edge of their distribution range are generally believed to be more fragmented, smaller, and exhibit lower genetic diversity and higher genetic differentiation, though several studies report the lack of this latitudinal trend (e.g. [ 56 ] and [ 57 ]). Edge populations are often subjected to biotic or abiotic environmental conditions not present in these core populations [ 55 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, populations at the edge of their distribution range are generally believed to be more fragmented, smaller, and exhibit lower genetic diversity and higher genetic differentiation, though several studies report the lack of this latitudinal trend (e.g. [ 56 ] and [ 57 ]). Edge populations are often subjected to biotic or abiotic environmental conditions not present in these core populations [ 55 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rodríguez et al. [29] conducted an experiment in the Canary Islands, Spain, in a controlled environment and revealed potential effectiveness of tracing apps in identifying simulated contacts. To summarize, these studies discovered that COVID-19 tracing apps could be effective under two conditions: i) many people adopt and employ the apps, and ii) infectious people should register their status on the apps.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we present an alternative 3-component mRNA vaccine utilizing mRNA encoding the receptor binding domain (RBD) of the SARS-CoV-2 spike protein formulated with a highly efficient, nontoxic, PEG-free mRNA delivery platform called charge-altering releasable transporters (CARTs) 14 16 and a TLR9 agonist (CpG) as a coformulated adjuvant 16 , 17 ( Figure 1 A). Prior studies had indicated that the RBD is a promising antigen target 18 20 as antibodies elicited against RBD are often strongly neutralizing. CARTs offer a promising new gene delivery platform and have proven to be effective deliverers of mRNA vaccines in preclinical mouse studies.…”
Section: Introductionmentioning
confidence: 99%